Intervensi Daring : Mengelola Sumber Daya Internal dan Eksternal Mahasiswa Untuk Beradaptasi Selama Pandemi COVID-19 - Clarissa Angelica Tjen; Catherine Nastasya; Nicholas Vincent; Shera Angelica; Yohana Ratrin Hestyanti (MADANI: Jurnal Pengabdian Kepada Masyarakat, 2022)
The COVID-19 pandemic has caused changes in various aspects, including academic, family, use of gadgets, and relationship between students. These changes have resulted in students experiencing negative impacts in their college life due to the difficulty in adapting in their classes. The purpose of the intervention is for students to have resource-management strategies in an academic context, especially in learning motivation, time management, and having a supportive social support to be able to adapt toward changes. The intervention used asynchronous and synchronous methods for the activities. The number of participants who took part in the intervention was 12 people. Overall, the social intervention process went smoothly and met several indicators of success. Based on the evaluation results, participants were satisfied with the implementation of the social intervention that had been carried out. Using non-parametric statistical analyses, results have shown that the participants' internal motivation and life satisfaction have significantly increased (p < .05), while their external motivation and perceived social support have not increased significantly. Despite the success of the intervention, there were also limitations. Researchers have found other variables that affect the intervention’s result. One of them is the duration of the social intervention which only lasted for two weeks, which resulted in participants not being able to form deep social connections optimally. In addition, there are extraneous variables that affect the results, which cannot be controlled by the researcher.